Cesium Doped NiOx as an Efficient Hole Extraction Layer for Inverted Planar Perovskite Solar Cells - Chen, Wei; Liu, Fang‐Zhou; Feng, Xi‐Yuan; Djurišić, Aleksandra B.; Chan, Wai Kin; He, Zhu‐Bing (Advanced energy materials, 2017)
Organic–inorganic hybrid perovskite solar cells have resulted in tremendous interest in developing next generation photovoltaics due to high record efficiency exceeding 22%. For inverted structure perovskite solar cells, the hole extraction layers play a significant role in achieving efficient and stable perovskite solar cell by modifying charge extraction, interfacial recombination losses, and band alignment. Here, cesium doped NiOx is selected as a hole extraction layer to study the impact of Cs dopant on the optoelectronic properties of NiOx and the photovoltaic performance. Cs doped NiOx films are prepared by a simple solution‐based method. Both doped and undoped NiOx films are smooth and highly transparent, while the Cs doped NiOx exhibits better electron conductivity and higher work function. Therefore, Cs doping results in a significant improvement in the performance of NiOx‐based inverted planar perovskite solar cells. The best efficiency of Cs doped NiOx devices is 19.35%, and those devices show high stability as well. The improved efficiency in devices with Cs:NiOx is attributed to a significant improvement in the hole extraction and better band alignment compared to undoped NiOx. This work reveals that Cs doped NiOx is very promising hole extraction material for high and stable inverted perovskite solar cells. Cesium doping of NiOx enhances the conductivity of the oxide film and the hole extraction from the perovskite film in inverted planar perovskite solar cells. Significantly improved photovoltaic performance is obtained with the best efficiencies of 16.04% and 19.35% for NiOx and Cs:NiOx, respectively. The devices exhibit negligible hysteresis and good stability.